Thromboembolic Risk in Newly Diagnosed Atrial Fibrillation Patient - Khatri, Ganga Ram; Murtuza, Shahid; Dhital, Bishnu Mani; Sah, Dayanand Prasad; Poudel, Srijana (Journal of National Heart and Lung Society Nepal, 2025)
Background: Atrial Fibrillation (AF) is commonest arrhythmias seen in clinical practice. The prevalence is 0.5% in patients under 60 years of age and 10% in patients above the age of 80 years. AF is most common arrhythmia in term of risk for thromboembolic events, which leaves vast scope for studying the thromboembolic risk in newly diagnosed atrial fibrillation. Methods: A hospital based descriptive observational study was conducted among 113 patients with first time documented atrial fibrillation on electrocardiogram without prior history of AF at Chitwan Medical College from November 2021 to December 2022.Results: Among113 patients mean age of the patients was 68.9 ± 14.8 years. 49, (43.4% ) had age more than 75 years old and 63,(55.8%) were females, Valvular AF was seen in 34,(30.1% ) while Non-valvular AF was 79,(69.9%) of cases. Among total patients 30.1 % with ValvularAF and out of 69.9% with Nonvalvular AF 68.3% patients who had CHA2DS2-VASc score of more than 2 were eligible for prevention from thromboembolic events. Conclusion: This study reﬂects the scenario of a patient presented with atrial fibrillation. Most of patient with AF were nonvalvular and among them majority of cases needs prevention for thromboembolism.